ESRA19-0313 Ultrasound-guided erector spinae plane (US-ESP) block associated with dexmetomidine cooperative sedation for anesthetic management in breast cancer surgery: a case report. (30th August 2019) - Giordano, C; Ranocchia, S; Nicolotti, D; Fusco, P; Danzi, V; Scimia, P
Abstract : Background and aims: Ultrasound-guided erector spinae plane block (US-ESPB) is a recently described regional block technique for anesthesia and analgesia of the chest wall. Dexmetomidine (DEX) is an α-2 agonist that can provide cooperative sedation during surgery. We reported a case of US-ESPB associated to intraoperative DEX sedation in a patient undergoing breast cancer surgery. Methods: A 42-year-old patient, ASA 2, was scheduled to undergo quadrantectomy with sentinel lymph node biopsy. Before surgery, we performed a US-ESPB and 20 ml of 0, 5% Ropivacaine were injected using a 90 mm needle (Temena®) deep to the erector spinae muscle and superficial to T5 transverse processes. The patient received intravenously DEX in a loading dose of 1 mcg/kg over 15 minutes, followed by an infusion of 0, 4 mcg/kg/h and oxygen (4 l/min) was administered by facemask. Results: We obtained adequate surgical anesthesia and a good quality postoperative analgesia. Moreover, DEX infusion provided cooperative sedation during surgery (Ramsay 3) without causing respiratory depression of the patient. Only 3 g of acetaminophen were administered postoperatively. No complications were recorded. Conclusions: This case report suggested that US-ESPB associated to intraoperative DEX cooperative sedation could represent a reliable strategy for anesthetic management in breast surgery.